KUSISDARI ON A MISSION EXPLORING UNIVERSITY OF HOKKAIDO - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, March 2017 Kumpulan SiswaSiswi Darul Ridzuan (KUSISDARI), Universiti Sains Malaysia (USM) recently organised a trip to explore the University of Hokkaido (UH), Japan with the aim of getting the students group to share their knowledge and experiences at the global stage.